FCTC ratification, smoking prevalence, and GDP per capita: lessons for Indonesia and the rest of the world - Abdillah Ahsan; Rifai Afin; Nadira Amalia; Martha Hindriyani; Ardhini Risfa Jacinda; Elisabeth Kramer (BMC, 2022)
Abstract Background Indonesia's stagnated progress towards tobacco control could be addressed through the implementation of a comprehensive national framework, such as the World Health Organization's (WHO) Framework Convention of Tobacco Control (FCTC). However, national tobacco industry supporters argue that accepting the FCTC will have negative economic implications for the country. These arguments have, thus far, discouraged the Indonesian government from ratifying the FCTC. Drawing from an analysis of the impact of the FCTC on other countries' smoking rates and Gross Domestic Product (GDP) per capita, this study offers empirical evidence against industry arguments concerning the potential negative economic impacts of FCTC adoption. This study applies a two stage least square estimation strategy to unbalanced panel data at country level. In the first stage we estimate the impact of FCTC ratification on smoking rates, and in the second step, we estimate the influence of smoking activity on macroeconomic performance. Results The result of this study shows that FCTC ratification has a negative impact on a country's smoking prevalence. While FCTC ratification positively correlates with reduced smoking prevalence, a decline in smoking prevalence is not related to a decline in GDP per capita. Conclusions The results of this study shows that FCTC ratification, which can be an important driver for more effective tobacco control, does not necessarily have a negative impact on the economy. Instead, FCTC ratification may be beneficial for both health and economic outcomes, as it provides comprehensive guidance for reducing smoking prevalence that take into account social and economic factors.